2019
DOI: 10.1038/s41467-019-08967-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free dehydropolymerisation of phosphine-boranes using cyclic (alkyl)(amino)carbenes as hydrogen acceptors

Abstract: The divalent carbene carbon centre in cyclic (alkyl)(amino)carbenes (CAACs) is known to exhibit transition-metal-like insertion into E–H σ-bonds (E = H, N, Si, B, P, C, O) with formation of new, strong C–E and C–H bonds. Although subsequent transformations of the products represent an attractive strategy for metal-free synthesis, few examples have been reported. Herein we describe the dehydrogenation of phosphine-boranes, RR’PH·BH3, using a CAAC, which behaves as a stoichiometric hydrogen acceptor to release m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 57 publications
(41 reference statements)
4
51
0
Order By: Relevance
“…12 More recently, Manners and co-workers have reported that treatment with stoichiometric quantities of cyclic alkyl amino carbenes (CAACs) induces the dehydrogenative coupling of phosphine-boranes to provide access to primary-and, previously unprecedented, secondary polyphosphinoboranes (Scheme 1b). 13 Of particular relevance to the current work is the B(C 6 F 5 ) 3 (BCF)-catalysed dehydropolymerisation of phosphine-borane and phenylphosphine-borane reported by Denis et al in 2003 (Scheme 1c). 14 This process was proposed to proceed via iterative borane transfer and dehydrocoupling steps involving a Brønsted-acidic phosphine-borane complex, (C 6 F 5 ) 3 B•PPhH 2 , as the active species.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…12 More recently, Manners and co-workers have reported that treatment with stoichiometric quantities of cyclic alkyl amino carbenes (CAACs) induces the dehydrogenative coupling of phosphine-boranes to provide access to primary-and, previously unprecedented, secondary polyphosphinoboranes (Scheme 1b). 13 Of particular relevance to the current work is the B(C 6 F 5 ) 3 (BCF)-catalysed dehydropolymerisation of phosphine-borane and phenylphosphine-borane reported by Denis et al in 2003 (Scheme 1c). 14 This process was proposed to proceed via iterative borane transfer and dehydrocoupling steps involving a Brønsted-acidic phosphine-borane complex, (C 6 F 5 ) 3 B•PPhH 2 , as the active species.…”
Section: Introductionmentioning
confidence: 88%
“…Thermal ellipsoids displayed at the 30% probability level with iso-propyl groups and hydrogen atoms omitted except those bound to boron. Selected bond lengths (Å) and angles (°): Ca1-N1 2.3147(14), Ca1-N2 2.2904(14), Ca1-C30 3.1365(19), Ca1-C31 3.044(2), Ca1-C32 2.905(2), Ca1-C33 2.843(2), Ca1-C34 2.9055(19), Ca1-C35 3.0416(19), Ca1-(C30-C35 centroid) 2.6391(10), Ca1-(C30-C35 centroid plane) 2.6215(11), P1-C37 1.8343(17), P1-C43 1.8382(16), P1-B1 1.9469(18), P1-B2 2.1368(18), C49-B2 1.640(2), C55-B2 1.640(2), C61-B2 1.639(2), C30-C31 1.388(3), C30-C35 1.396(3), C30-C36 1.502(3), C31-C32 1.389(3), C32-C33 1.381(3), C33-C34 1.379(3), C34-C35 1.383(3), N1-Ca1-(C30-C35 centroid) 110.05(5), N1-Ca1-(C30-C35 normal) 105.58(7), N2-Ca1-(C30-C35 centroid) 109.50(4), N2-Ca1-(C30-C35 centroid) 114.48(7), N2-Ca1-N1 84.76(5), C30-C31-C32 120.7(2), C33-C32-C31 120.3(2), C34-C33-C32 119.8 (2), C33-C34-C35 119.9(2), C34-C35-C30 121.2(2), C37-P1-C43 103.82(7), C37-P1-B1 105.99(8), C37-P1-B2 109.52(7), C43-P1-B1 106.29(8), C43-P1-B2 114.17(7), B1-P1-B2 116.06(7), C49-B2-P1 110.52(11), C49-B2-C55 111.11(13), C55-B2-P1 104.30(10), C61-B2-P1 102.97(11), C61-B2-C49 114.13(13), C61-B2-C55 113.02(13). Synthesis of compound 4a.…”
mentioning
confidence: 99%
“…Therefore, cAACs cannot behave like transition-metal centers in synthetic utility. Manners et al [308] anticipated that a cAAC-mediated dehydrogenation of primary and secondary phosphine-boranes, species that contain both protic PÀ H and hydridic BÀ H bonds, might be possible (Scheme 69c). Dehydrogenation of phosphine-boranes utilizing this strategy gives reactive phosphinoborane monomers, with appropriate substituents at the phosphorus and boron centers.…”
Section: Polymerization Reactions By Caac-containing Compoundsmentioning
confidence: 99%
“…Therefore, cAACs cannot behave like transition‐metal centers in synthetic utility. Manners et al [308] . anticipated that a cAAC‐mediated dehydrogenation of primary and secondary phosphine‐boranes, species that contain both protic P−H and hydridic B−H bonds, might be possible (Scheme 69c).…”
Section: Areas Of Caac Chemistrymentioning
confidence: 99%
“…However, the products were not unambiguously characterised and, where reported, yields and molar masses were very low. Attempts to apply current catalytic routes towards P-disubstituted polyphosphinoborane targets by dehydrocoupling of secondary phosphine boranes, RR′PH-BH 3 , have been unsuccessful to date, yielding instead small rings or oligomeric materials 2b,4a,c,e,6. High molar mass P-disubstituted polyphosphinoboranes would be devoid of P–H bonds and are likely to be the most thermally and environmentally robust and therefore the most realistically useful in applications.…”
Section: Introductionmentioning
confidence: 99%